2012
DOI: 10.1177/1934578x1200700530
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antibacterial Activity of the Essential Oil of Espeletia nana

Abstract: The essential oil of the leaves of Espeletia nana Cuatrec., obtained by hydrodistillation, was analyzed by GC-MS, which allowed the identification of 24 components, which made up 99.9% of the oil. The most abundant compounds were α-pinene (38.1%), β-pinene (17.2%), myrcene (15.0%), spathulenol (4.2%), bicyclogermacrene (4.0%), -zingiberene (4.0%), and -himachalene (3.7%). Antibacterial activity was tested against Gram-positive and Gramnegative bacteria using the agar disk diffusion method. Activity was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…These substances exert their toxic effect against some microorganisms through disruption of their membrane integrity, inhibiting respiration and ion transport processes [5c] . There are no previous reports on either the chemical composition or antimicrobial activity of the essential oil of R. Bracteosa, but similar antimicrobial activity against Gram-positive bacteria was reported by Peña et al [6] for the essential oil of Espeletia nana. The most abundant compounds of E. nana oil were α-pinene (38.1%), β-pinene (17.2%), and myrcene (15.0%).…”
supporting
confidence: 56%
“…These substances exert their toxic effect against some microorganisms through disruption of their membrane integrity, inhibiting respiration and ion transport processes [5c] . There are no previous reports on either the chemical composition or antimicrobial activity of the essential oil of R. Bracteosa, but similar antimicrobial activity against Gram-positive bacteria was reported by Peña et al [6] for the essential oil of Espeletia nana. The most abundant compounds of E. nana oil were α-pinene (38.1%), β-pinene (17.2%), and myrcene (15.0%).…”
supporting
confidence: 56%
“…It can contribute up to 30% of the essential oils in ginger rhizomes. 24 ZBN has several pharmacological properties such as antioxidant, 25 anticancer, 26 antiulcer, 27 antibacterial, 28 and antiviral 29 effect. ZBN possess the ability to modulate the inflammatory PI3K/AKT/mTOR pathway in human cells.…”
Section: Introductionmentioning
confidence: 99%
“…It can contribute up to 30% of the essential oils in ginger rhizomes. 21 The limited numbers of recent investigations have revealed that ZGB exhibits many important biological activities, including antioxidant activity, 22 anticarcinogenic activity, 23 antiulcer activity, 24 antibacterial activity 25 and antiviral activity. 26 However, whether ZGB exerts protective effects against oxidative cytotoxicity in neuronal models as a result of its antioxidant property has not been investigated.…”
Section: Introductionmentioning
confidence: 99%